Atchafalaya Houseboat : My Years in the Louisiana Swamp - Roland, Gwen, 1948- (Book collections on Project MUSE., 2006)
In the early 1970s, two idealistic young people⁰́₄Gwen Carpenter Roland and Calvin Voisin⁰́₄decided to leave civilization and re-create the vanished simple life of their great-grandparents in the heart of Louisiana's million-acre Atchafalaya River Basin Swamp. Armed with a box of crayons and a book called How to Build Your Home in the Woods, they drew up plans to recycle a slave-built structure into a houseboat. Without power tools or building experience they constructed a floating dwelling complete with a brick fireplace. Towed deep into the sleepy waters of Bloody Bayou, it was their home for eight years. This is the tale of the not-so-simple life they made together⁰́₄days spent fishing, trading, making wine, growing food, and growing up⁰́₄told by Gwen with grace, economy, and eloquence.Not long after they took up swamp living, Gwen and Calvin met a young photographer named C. C. Lockwood, who shared their "back to the earth" values. His photographs of the couple going about their daily routine were published in National Geographic magazine, bringing them unexpected fame. More than a quarter of a century later, after Gwen and Calvin had long since parted, one of Lockwood's photos of them appeared in a National Geographic collector's edition entitled 100 Best Pictures Unpublished⁰́₄and kindled the interest of a new generation.With quiet wisdom, Gwen recounts her eight-year voyage of discovery⁰́₄about swamp life, wildlife, and herself. A keen observer of both the natural world and the ways of human beings, she transports readers to an unfamiliar and exotic place.